Constraints on Transient Viscoelastic Rheology of the Asthenosphere From Seasonal Deformation. Issue 5 (15th March 2018) - Chanard, Kristel; Fleitout, Luce; Calais, Eric; Barbot, Sylvain; Avouac, Jean‐Philippe
Abstract: We discuss the constraints on short‐term asthenospheric viscosity provided by seasonal deformation of the Earth. We use data from 195 globally distributed continuous Global Navigation Satellite System stations. Surface loading is derived from the Gravity Recovery and Climate Experiment and used as an input to predict geodetic displacements. We compute Green's functions for surface displacements for a purely elastic spherical reference Earth model and for viscoelastic Earth models. We show that a range of transient viscoelastic rheologies derived to explain the early phase of postseismic deformation may induce a detectable effect on the phase and amplitude of horizontal displacements induced by seasonal loading at long wavelengths (1, 300–4, 000 km). By comparing predicted and observed seasonal horizontal motion, we conclude that transient asthenospheric viscosity cannot be lower than 5 × 10 17  Pa.s, suggesting that low values of transient asthenospheric viscosities reported in some postseismic studies cannot hold for the seasonal deformation global average. Key Points: We model global seasonal horizontal and vertical surface displacements induced by loading derived from GRACE in a viscoelastic framework We show that viscosities derived to explain early postseismic deformation may yield a detectable effect on horizontal seasonal displacements Asthenospheric viscosity lower bound from seasonal deformation suggesting some postseismic studies cannot hold for the global average